Managing the challenges of competing interests of different regions in setting the boundaries of neighboring urban areas: the case of Addis Ababa city administration and oromia regional state, Ethiopia. Issue 10 (October 2022) - Benti, Solomon; Terefe, Heyaw; Callo-Concha, Daniel
Abstract: In Ethiopia, urban boundary roles are ineffective, leading to conflicting urban development, particularly on areas share borders and are administered by different regional governments. Therefore, this study examined the nature of shared urban boundaries and related social-ecological challenges. It employed a case study approach, and the findings are conceptualized to the broader urbanization and urban planning trends, with particular relevance to any urban areas sharing borders. Temporal satellite images from 2005 and 2018 were used to examine land use/land cover changes around shared urban regions, and their proposed and existing land-uses were compared with the aid of Geographical Information System and ERDAS IMAGINE. The findings show lack of clear criteria to delineate urban boundaries in Ethiopian urban planning; absence of regional planning leading to indistinct and overlapping boundary setting, which triggered challenges related to: rapid conversion of ecosystem service providing sites to settlements, conflicts over land administration, and land ownership insecurity. Furthermore, non-integrated urban planning trends between urban areas sharing borders amplify the proposal of conflicting and incompatible land uses. As a result, policymakers and planners should employ integrated and participatory urban and regional planning concepts for the effectiveness of urban areas sharing boundaries and administered by different regions. Abstract : Border towns; Urban boundary; Integrated urban planning; Regional planning; Social-ecological challenges.